PEDANG MEBEL TEKNIK PEMBUATAN DAN PENGGUNAAN MEDIA PEMBELAJARAN: UPTD SPF SDN PANCURAN 1 BONDOWOSO - SITI MUTAWARRIDAH (Mitra Pendidikan, 2022)
The purpose of this study is to improve teacher competence in the manufacture and use of instructional media at SDN Pancuran 1 Bondowoso. The benefit is that it can develop knowledge and skills in making learning media, helping teachers find alternatives for making learning media that can increase student learning motivation. Helping teachers to increase commitment, willingness, and motivation in carrying out their duties. The implementation of training and assistance for the creation and use of instructional media is very effective. This can be seen in the increase in the activity of each cycle. The results achieved increased from cycle 1 to get a value of 73.61 in cycle 2 to get a value of 86.11. Thus in the second cycle the teacher was able to create and use learning media.